Comparison of Perioperative Outcomes of Autologous Bladder Neck Fascial Slings Based on Fascial Harvest Site: A Secondary Analysis of the National Surgical Quality Improvement Program Database. Issue 8 (August 2020) - Cardenas-Trowers, Olivia O.; Stewart, Ryan; Meriwether, Kate V.; Francis, Sean; Gupta, Ankita
Abstract : Objectives: The objective of this study was to compare perioperative outcomes of autologous bladder neck fascial slings (ABNFS) between rectus fascia and fascia lata harvest sites. Methods: We analyzed women undergoing ABNFS in the 2006 to 2015 American College of Surgeons National Surgical Quality Improvement Program database, separating rectus fascia and fascia lata harvest sites by Current Procedural Terminology codes. We compared the 2 harvest sites for perioperative outcomes within 30 days including adverse events, readmission, and reoperation as well as operative time and length of hospital stay. The primary outcome was a composite of postoperative adverse events, readmission, and reoperation. A multivariable logistic regression model was used incorporating race, smoking status, surgical specialty, anesthesia class, concurrent procedures, body mass index, operating time, and length of hospital stay. Results: A total of 161 women in the database underwent ABNFS: 126 (78.3%) rectus fascia and 35 (21.7%) fascia lata harvest. Patients undergoing rectus fascial harvest were more likely to be white (140 [90.5%] rectus vs 26 [74.3%] fascia lata, P =0.02) and more likely to have ABNFS by a urologist (117 [93%] rectus vs 23 [66%] fascia lata, P < 0.01). There were no significant differences in operative time, length of stay, rate of reoperation, nonserious or serious adverse events, or readmission between the 2 harvest site groups. The 2 harvest sites had similar composite morbidity (adjusted odds ratio of 0.88 for rectus fascia; 95% confidence interval, 0.21–3.75; P =0.87). Conclusions: Rectus fascia and fascia lata harvest for ABNFS have similar perioperative outcomes.